Friction Stir welding of Light Metals for Industrial Applications. (2015) - Grimm, A.; Schulze, S.; Silva, A.; Göbel, G.; Standfuss, J.; Brenner, B.; Beyer, E.; Füssel, U.
Abstract: The high potential of Friction Stir Welding (FSW) is already widely used in industrial applications. In combination with a suitable machine concept, this technology is appropriate for small components and can be extended to applications on structures of several meters in length. Using a 3D-capable system that is stiff enough to handle the high process forces, machining and friction stir welding of complex geometries can be carried out directly in one set-up. In order to ensure reproducible, high quality welds, appropriate control strategies are needed. Furthermore the use of various tool types such as standard or bobbin tools can extend the range of weldable geometries tremendously. The aforementioned aspects have been part of process development work for FSW at Fraunhofer IWS Dresden in the last few years. Within the current paper interesting findings are discussed in detail. This includes the realization of a fully 3D-capable FSW machine based on a so-called Pentapod concept. This parallel-kinematic system is suitable for large and complex three-dimensional structures up to 7 meters in length. The FSW research is focused on the welding of aircraft structures and mixed-material joints; examples of research projects and their results are given. Selected welding examples of wrought and cast aluminum, high strength alloys and copper will be presented as well as experiences, which have been made in terms of process development and process control.